Analysis of the Effect of Tax Avoidance, Capital Structure, Debt Policy, Managerial Ownership, and Environmental Performance on Firm Value - Azami, Washil; Achyani, Fatchan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine the effect of tax avoidance, capital structure, debt policy, managerial ownership, and environmental performance on firm value in mining companies listed on the Indonesia Stock Exchange during 2021–2024. The research employs a quantitative approach grounded in positivism, using panel data derived from annual reports and PROPER environmental ratings. The sample consists of mining companies selected through purposive sampling based on specific criteria. Firm value is measured using Price to Book Value (PBV), while independent variables are proxied by relevant financial ratios and environmental performance ratings. Data analysis includes descriptive statistics, classical assumption tests, and panel data regression with model selection through Chow, Hausman, and Lagrange Multiplier tests at a 5% significance level. The results indicate that capital structure and managerial ownership have a positive and significant effect on firm value, whereas tax avoidance, debt policy, and environmental performance do not significantly influence firm value. These findings suggest that financial structure and internal ownership play a more substantial role in determining market valuation than tax strategy and environmental performance within the observed period.